Antibody engineering & therapeutics, the annual meeting of the antibody society December 7–10, 2015, San Diego, CA, USA. Issue 3 (2nd April 2016) - Pauthner, Matthias; Yeung, Jenny; Ullman, Chris; Bakker, Joost; Wurch, Thierry; Reichert, Janice M.; Lund-Johansen, Fridtjof; Bradbury, Andrew R.M.; Carter, Paul J.; Melis, Joost P.M.
ABSTRACT: The 26th Antibody Engineering & Therapeutics meeting, the annual meeting of The Antibody Society united over 800 participants from all over the world in San Diego from 6–10 December 2015. The latest innovations and advances in antibody research and development were discussed, covering a myriad of antibody-related topics by more than 100 speakers, who were carefully selected by The Antibody Society. As a prelude, attendees could join the pre-conference training course focusing, among others, on the engineering and enhancement of antibodies and antibody-like scaffolds, bispecific antibody engineering and adaptation to generate chimeric antigen receptor constructs. The main event covered 4 d of scientific sessions that included antibody effector functions, reproducibility of research and diagnostic antibodies, new developments in antibody-drug conjugates (ADCs), preclinical and clinical ADC data, new technologies and applications for bispecific antibodies, antibody therapeutics for non-cancer and orphan indications, antibodies to harness the cellular immune system, building comprehensive IgVH-gene repertoires through discovering, confirming and cataloging new germline IgVH genes, and overcoming resistance to clinical immunotherapy. The Antibody Society's special session focused on "Antibodies to watch" in 2016. Another special session put the spotlight on the limitations of the new definitions for the assignment of antibody international nonproprietary names introduced by the World Health Organization. The convention concluded with workshops on computational antibody design and on the promise and challenges of using next-generation sequencing for antibody discovery and engineering from synthetic and in vivo libraries.